1994
DOI: 10.1111/j.1365-3059.1994.tb01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Canker and die‐back of Eucalyptus in South Africa caused by Botryosphaeria dothidea

Abstract: Die‐back and canker of several Eucalyptus species and clones were observed during a survey of the most important forestry areas of South Africa. Disease was often associated with extreme environmental conditions such as drought, hot winds and frost. Botryosphaeria dothidea, which is well known as a cause of canker and die‐back of Eucalyptus in other countries, was consistently isolated from symptomatic trees. Artificial inoculations of Eucalyptus nitens resulted in lesion development, confirming the pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…Species with a wide host range often also behave as latent pathogens (Slippers et al 2005a;Slippers et al 2005b) and ) with the ability to cause disease symptoms on hosts, as shown in pathogenicity trials (Fraser and Davison 1985;Shearer et al 1987) Smith et al 1994) and as disease records in the field (Barnard et al 1987;Fraser and Davison 1985;Shearer 1994;Úrbez-Torres et al 2008). Some of the Botryosphaeriaceae exhibit a very restricted host range such as D. santalui restricted to S. acuminatum, and D. moneti restricted to A. rostellifera and A. cochlearis (Taylor et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Species with a wide host range often also behave as latent pathogens (Slippers et al 2005a;Slippers et al 2005b) and ) with the ability to cause disease symptoms on hosts, as shown in pathogenicity trials (Fraser and Davison 1985;Shearer et al 1987) Smith et al 1994) and as disease records in the field (Barnard et al 1987;Fraser and Davison 1985;Shearer 1994;Úrbez-Torres et al 2008). Some of the Botryosphaeriaceae exhibit a very restricted host range such as D. santalui restricted to S. acuminatum, and D. moneti restricted to A. rostellifera and A. cochlearis (Taylor et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many members have a broad host range (Punithalingam 1976(Punithalingam , 1980, they fruit on senescing tissue , are found in above ground plant parts (Johnson et al 1992) and multiple species are found often within localised infections in the host tissue (Sakalidis et al 2011a, b;Spagnolo et al 2011). However; unlike other Class III fungi they have occasionally been observed in host seeds (Johnson et al 1998;Bihon et al 2011) and there is also evidence of infections in horticultural crops occurring via pruning wounds (Brown and Hendrix 1981;Smith et al 1994Smith et al , 1996Amponsah et al 2011;Sakalidis et al 2011c). Pathogenicity trials are successfully used to prove potential for disease development (Amponsah et al 2011;Sakalidis et al 2011c) but little is known about possible passive (endophytic) or delayed active (latent pathogen) life stages that may also initiate from the same infections.…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that B. ribis and B. euclayptorum obtained from the lesions analyzed in this study were not the causal agents of the symptoms observed in plantations. Conversely, the experimental infection with Botryosphaeria species on Eucalyptus in South Africa resulted in bark lesions of different entities (SMITH et al, 1994). It is probable that there is a susceptibility variation among Eucalyptus species (SMITH et al, 1996) as well as variation in virulence of Botryosphaeria strains (SMITH et al, 2001).…”
Section: Results and Discusionmentioning
confidence: 99%
“…C. eucalypticola Van der Weisthuizen and Botryosphaeria spp. are commonly associated with stem cankers and are considered opportunistic pathogens (SMITH et al, 1994). Colletogloeopsis zuluense Wingf., Crous & Cout.…”
Section: Introductionmentioning
confidence: 99%